Silencing MIG1 in Saccharomyces cerevisiae: effects of antisense MIG1 expression and MIG1 gene disruption. - Olsson, L (1997)
Silencing of MIG1, a transcription factor imposing carbon catabolite repression on invertase, was attempted, either by disrupting the gene or by expressing antisense copies of the gene. The performance of the recombinant strains in bioreactor batch cultivations on sucrose, in the presence of glucose, was compared with that of the wild-type strain under the same conditions. In the delta migI strain, the rate of sucrose utilization was independent (10 mmol/g/h) of the glucose concentration. During the cultivations with the wild-type strain and the antisense strains, two distinct phases were observed. The rates of sucrose hydrolysis were < 1 mmol/g/h and 9 to 10 mmol/g/h in the first and second phases, respectively. Entry into the second cultivation phase was characterized by a decline in glucose concentration below 12 mmol/liter. As expected, disruption of MIG1 resulted in a relief of glucose repression. However, silencing of MIG1 expression was not achieved by expressing antisense MIG1, even though antisense MIG1 RNA was sufficiently stable to be detected. In the wild-type and delta migI strains, the specific growth rate was 0.32 to 0.33 h-1, whereas it was lower in the antisense strains, 0.25 to 0.30 h-1.